Developing Comic Strips in Teaching Vocabulary for EFL Students - Novi Rahmania Aquariza; Rudi Umar Susanto (STAI Nurul Islam Mojokerto, 2023)
There are various ways that can be taken to improve the vocabulary of EFL students. The use of media, as well as teaching methods. This research focuses on developing Comic Strips as a supporting medium for vocabulary teaching. Based on the sections from Comic Strips, students can choose what vocabulary they want to use to complete the available bubbles so that they form sentences and in the end a coherent story. Lecturers can also use Comic Strips to facilitate students in developing ideas in their writings by asking some stimulating questions. In line with the usefulness of Comic Strips to improve the vocabulary of EFL students, the researchers developed comic strip media with certain themes to be used in vocabulary courses for 7 meetings. The researcher believes that the development of Comic Strips media can be effective because it can make students enjoy the teaching and learning process.